Leptin/Adiponectin Ratios Using Either Total Or High-Molecular-Weight Adiponectin as Biomarkers of Systemic Insulin Sensitivity in Normoglycemic Women. (25th May 2017) - Bravo, Carolina; Cataldo, Luis Rodrigo; Galgani, José; Parada, Javier; Santos, José Luis
Abstract : Plasma leptin/adiponectin ratio (LAR) is negatively associated with insulin sensitivity indexes. High-molecular-weight adiponectin (HMWA) was proposed as the most biologically active form of this insulin-sensitizing adipokine. There are no studies assessing the relative merits of leptin/HMWA ratio over LAR as a biomarker of systemic insulin sensitivity. A standard 2-hour oral glucose tolerance test (OGTT; 75 g of glucose) and a short minimal-model intravenous glucose tolerance test (IVGTT; 0.3 g/kg body weight) were performed in 58 Chilean normoglycemic women (age: 27 ± 6.3 years, BMI 23.6 ± 3.2 kg/m 2 ). LAR was negatively associated with HOMA-S (r = − 0.49 ; p < 0.0001 ), Matsuda-ISICOMP (r = − 0.54 ; p < 0.0001 ), and the calculated sensitivity index (CSi) derived from IVGTT (r = − 0.38 ; p = 0.007 ). In comparison to LAR, leptin/HMWA ratio did not increase neither the linear fit (r 2 ) nor the magnitude of association with insulin sensitivity indexes (slope of multiple linear regression). The discriminatory capacity of both ratios to classify insulin-resistant versus insulin-sensitive subjects was similar for HOMA-S (p = 0.84 ), Matsuda-ISICOMP (p = 0.43 ), or CSi (p = 0.50 ). In conclusion, LAR showed consistent negative associations with different systemic insulin sensitivity indexes. The use of HMWA to generate leptin/HMWA ratio did not show any advantage over LAR as a biomarker of systemic insulin sensitivity in normoglycemic women.